Motivating Students in Learning English Using Icebreaking - Anita Rezki; Abdul Halim; Tegar Sentosa (AL LUGHAWIYAAT, 2022)
This qualitative study explored to what extent ice breaking motivates students to learn English at one of the Islamic states junior high school in Southeast Sulawesi. This study employs two methods: a questionnaire and reflective writing. This study used two instruments: questionnaire and reflection. Students were handed questionnaires twice, at the beginning of the meeting before implementing Icebreaking and at the end of the meeting after implementing Icebreaking, in order to observe improvements and significantly increase student motivation. At the end of the meeting, in addition to providing in-depth information, the researcher provided reflection so that students may describe more precisely what they felt and gained during the Icebreaking application. This study revealed two aspects: motivation and Attraction. Aspects pertaining to motivation indicate that Icebreaking motivates students to study English. While the intriguing feature exposed by Icebreaking helps students avoid boredom during the teaching and learning process and increases their enjoyment of class activities. In addition, a number of students reported that English became their favorite subject.Keyword: Icebreaking, learning English, Students’ Motivation